Nomophobia Phenomena Analysis at SDN 2 Bembulang - Alfi Mukhlis Kurniawan; Amalia Nurul Azizah (Universitas Sebelas Maret, 2022)
Nomophobia is a term used to describe the fear of losing or not being able to use a cell phone. This study aims to analyze the phenomenon of nomophobia among students of SDN 2 Bembulang. The research method used is a qualitative method with a case study approach. Data collection was carried out through observation, in-depth interviews, and documentation studies. The results of the study show that nomophobia is common among students at SDN 2 Bembulang. Causes of nomophobia among such students include technology addiction, peer pressure, and the need to be constantly connected. The effects of nomophobia among such students include decreased academic performance, social withdrawal, and physical health problems. The findings from this study suggest the need for intervention and education programs to help SDN 2 Bembulang students manage their cell phone use and prevent nomophobia.